2015
DOI: 10.1534/genetics.115.175166
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Enhancement of Genome Editing by CRISPR/Cas9 Through Improved Guide RNA Design

Abstract: Success with genome editing by the RNA-programmed nuclease Cas9 has been limited by the inability to predict effective guide RNAs and DNA target sites. Not all guide RNAs have been successful, and even those that were, varied widely in their efficacy. Here we describe and validate a strategy for Caenorhabditis elegans that reliably achieved a high frequency of genome editing for all targets tested in vivo. The key innovation was to design guide RNAs with a GG motif at the 39 end of their target-specific sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
232
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(237 citation statements)
references
References 48 publications
2
232
1
2
Order By: Relevance
“…To verify that rbm-5 mutations can suppress the ts-lethality of uaf-1(n4588) mutants, we used a modified CRISPR/Cas9 method [41] to generate new mutations in rbm-5 (Figure 3(a), sgRNA1, sgRNA2, sgRNA3 ). By this approach, we obtained five deletion mutations in rbm-5 (Figure 3(a) and Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify that rbm-5 mutations can suppress the ts-lethality of uaf-1(n4588) mutants, we used a modified CRISPR/Cas9 method [41] to generate new mutations in rbm-5 (Figure 3(a), sgRNA1, sgRNA2, sgRNA3 ). By this approach, we obtained five deletion mutations in rbm-5 (Figure 3(a) and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…We followed the method by Farboud et al [41] with minor modifications. Plasmids for microinjection were purified using OMEGA’s Midi Plasmid Purification kit (Omega Bio-tek).…”
Section: Methodsmentioning
confidence: 99%
“…But short arms also mean that the cut site must be very close to the targeted insertion site (in our experiments separated by only 4-20 bp), which limits selection of the guide RNA binding site. The Meyer group recently demonstrated that guide RNAs that bind to sites with a diguanine motif immediately preceding the PAM sequence (called ggNGG guides) are significantly more efficient at generating double-stranded breaks in the worm genome in vivo (Farboud and Meyer 2015). Binding sites containing the ggNGG motif are significantly less common than binding sites containing only the NGG PAM sequence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a highest cleavage efficiency was observed in C. elegans when the final 6 bp of the protospacers of Sp-derived sgRNAs contained 4 or more GCs [39]. Identically, a better frequency of cleavage and homology-driven gene knock-in was demonstrated in C. elegans with protospacers ending with a GG motif [40]. This could be due to the fact that a high proportion of GCs close to the PAM would make the Cas9 stay longer on the target and give it more chance of cutting.…”
Section: Selection Of Target Sitesmentioning
confidence: 97%